Prevalence of traditional cardiovascular risk factors in high-risk Kyrgyzstan population as compared to Indians − An Indo-Kyrgyz cardiometabolic study - Kamal Sharma; Shilpi Mohan; S. A. Hossain; Stuti Shah; Ashwati Konat; Komal Shah; Shubh Mehta; Jonsi Jayantkumar Tavethia; Jeel Narendra Sarvaiya; Saumya Joshi; Karan Shah; Dhruv Rakeshkumar Patel; et al. (Journal of Family Medicine and Primary Care)
Background: Cardiovascular diseases (CVDs) are one of the most prevalent causes of mortality worldwide, especially significant in low- and middle-income countries. Kyrgyzstan and India represent such nations that face a huge burden of CVD-related deaths globally. Understanding the prevalence of traditional cardiovascular risk factors (CVRFs) in these populations is critical for effective prevention and management strategies. Methods: This is a multicentric, observational study where we compared the prevalence of CVRFs in high-risk populations from Kyrgyzstan and India. Data was collected from established ASCVD patients attending cardio-metabolic clinics at tertiary care centers between December 2021 and December 2023. Demographic characteristics and CVRFs, which encompassed diabetes, hypertension, lipid profile parameters, tobacco consumption, etc., were assessed. Statistical analysis was performed to identify significant differences between the cohorts. Results: A total of 1552 individuals (772 from Kyrgyzstan, 750 from India) were studied. The Kyrgyzstan cohort had a significantly higher mean age and a greater proportion of females compared to the Indian cohort. The prevalence of tobacco consumption, hypertension, and diabetes was significantly higher in Kyrgyzstan than in India. Lipid profile analysis revealed greater level of LDL, HDL, and total cholesterol in the Kyrgyzstan cohort. Conversely, triglyceride levels were lower in Kyrgyz individuals. The Kyrgyzstan cohort also demonstrated better left ventricular systolic function compared to the Indian cohort. Discussion: Our study highlights significant differences in the prevalence of traditional CVRFs between high-risk populations in Kyrgyzstan and India. Higher rates of tobacco consumption, hypertension, and diabetes in Kyrgyzstan signify the immediate need for targeted interventions to address these modifiable risk factors. Targeted public health programs focusing on these lifestyle modifications and efficacious management of CVRFs are crucial to reduce the burden of cardiovascular deaths in both countries.